The Effectiveness of Dual Strategies in Learning to Write Prophetic Paragraphs via Google Form File Upload - Rika Widawati; Ratih Kirana Suryo Puteri; Ani Rachmat (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe: 1) the results of the pre-test of writing prophetic paragraphs; 2) the results of the post-test of writing prophetic paragraphs in learning using Google Form file upload; 3) the effectiveness of the dual strategy in learning to write prophetic paragraphs using Google Form file upload. The dual strategy referred to in this article is the process skills approach, model method, test techniques, and copying task techniques. This study used a quantitative descriptive method conducted in the odd semester of the 2025/2026 academic year at the Indonesian University of Education. The population of this study was new students of the Islamic Religious Education Study Program in the 2025/2026 academic year who participated in learning to write prophetic paragraphs using Google Forms and submitted the initial and final tests via Google Forms. They numbered 40 students from one class. The sample was determined to be 37 students based on statistical formulas and selected using a simple random sampling technique without replacement. The Prophetic Paragraph Writing Test instrument was used to collect data for both the pretest and post-tests. The test instrument was prepared in accordance with the test specifications to meet the requirements for a valid instrument. The pre-test and post-test data were analyzed using parametric inferential statistics, namely the one-sample t-test, while the effectiveness was analyzed using the paired sample t-test. The results of the study showed: 1) the results of the pre-test for writing prophetic paragraphs were categorized according to the expected mean, namely the B- value category; 2) the results of the post-test for writing prophetic paragraphs through learning using a dual strategy in the Google Form file upload option were categorized according to the expected mean, namely the A- value category; 3) the dual strategy was effectively used in learning to write prophetic paragraphs using the Google Form file upload in the Islamic Religious Education Study Program, Universitas Pendidikan Indonesia.